Activated protein C ameliorates LPS-induced acute kidney injury and downregulates renal INOS and angiotensin 2 - Gupta, Akanksha; Rhodes, George J; Berg, David T; Gerlitz, Bruce; Molitoris, Bruce A; Grinnell, Brian W (American journal of physiology. Renal physiology, 2007)
Endothelial dysfunction contributes significantly to acute renal failure (ARF) during inflammatory diseases including septic shock. Previous studies have shown that activated protein C (APC) exhibits anti-inflammatory properties and modulates endothelial function. Therefore, we investigated the effect of APC on ARF in a rat model of endotoxemia. Rats subjected to lipopolysaccharide (LPS) treatment exhibited ARF as illustrated by markedly reduced peritubular capillary flow and increased serum blood urea nitrogen (BUN) levels. Using quantitative two-photon intravital microscopy, we observed that at 3 h post-LPS treatment, rat APC (0.1 mg/kg iv bolus) significantly improved peritubular capillary flow [288 +/- 15 microm/s (LPS) vs. 734 +/- 59 microm/s (LPS+APC), P = 0.0009, n = 6], and reduced leukocyte adhesion (P = 0.003) and rolling (P = 0.01) compared with the LPS-treated group. Additional experiments demonstrated that APC treatment significantly improved renal blood flow and reduced serum BUN levels compared with 24-h post-LPS treatment. Biochemical analysis revealed that APC downregulated inducible nitric oxide synthase (iNOS) mRNA levels and NO by-products in the kidney. In addition, APC modulated the renin-angiotensin system by reducing mRNA expression levels of angiotensin-converting enzyme-1 (ACE1), angiotensinogen, and increasing ACE2 mRNA levels in the kidney. Furthermore, APC significantly reduced ANG II levels in the kidney compared with the LPS-treated group. Taken together, these data suggest that APC can suppress LPS-induced ARF by modulating factors involved in vascular inflammation, including downregulation of renal iNOS and ANG II systems. Furthermore, the data suggest a potential therapeutic role for APC in the treatment of ARF.